Influência do tratamento endodôntico sobre a espessura dentinária na região da concavidade mesial do 1o . pré-molar superior. - Rosalem, Cíntia Gonçalves Carvalho (2015)
Introduction: The root concavities may influence the dental treatment. Variations in root morphology are suggested as the main cause of perforations and other types of failures. The decrease in dentin thickness in the wall of the root canal in teeth subjected to endodontic treatment can be aggravated by procedures such as scaling and root planing and preparation for intracanal posts, especially in areas where the concavity is present. Objective: To evaluate the influence of root concavity mesial on the thickness and volume of dentin of maxillary first premolars before and after endodontic instrumentation and scaling and root planing. Methods: Twenty-seven firts premolars were analyzed for the presence of the proximal concavity. The teeth were then evaluated using the method of computed microtomography (micro-CT), where the thickness and the volume of dentin was examined. The teeth were scanned again after endodontic instrumentation and scaling and root planing. The data were submitted to descriptive statistical analysis. To evaluate the dentin thickness was used t test for paired samples and to evaluate the dentin volume, the Wilcoxon test (p <0.05). Results: The root concavities were present in all mesial surfaces of teeth examined. The dentin thickness in the region of the concavities decreased in millimeters, of 1.81 ± 0.25 to 1.55 ± 0.26 (p <0.001) and decreased dentin volume in cubic millimeters of 148.37 ± 43 53 to 140.36 ± 37.09 (p <0.001) after endodontic instruments and scaling and root planing. Conclusion: It can be concluded that the root concavities were present in 100% of the analyzed teeth. The dentin thickness in the region of the concavities decreased considerably after endodontic instruments and scaling and root planing, and the volume of dentin at the cervical third of the root also reduced after the treatments.